Faktor - Faktor Pendukung Keputusan Rujukan Pasien pada Fasilitas Kesehatan Tingkat Pertama (FKTP) dengan metode Analytical Hierrarchy Process (AHP) - Hilyah Magdalena; Hadi Santoso; Dita Meliansari (METIK JURNAL, 2021)
Pratama Bakti Timah Clinic is one of the First Level Health Facilities (FKTP) that provides health services to the community in the Pangkalpinang area and its surroundings. In these health service activities, when a patient requires special medical care in terms of medical services, medical personnel, medical support, outpatient services, and inpatient services, the patient will be referred to a higher health facility. Considering the various factors that cause patients to be referred and there are several hospitals that are referred to, this condition is a multi-criteria and multi-alternative condition. To overcome this, it is necessary to design a decision support system that will make it easier for medical administration service officers at the Primary Clinic. The decision support system is designed using the Analytical Hierarchy Process (AHP) method which is able to accommodate multi-criteria and multi-alternative decision making. The results of data processing showed that the most important factor in the referral of FKTP patients at the Pratama Clinic was the outpatient service factor with a weight of 30.7%, the second factor was medical services 24.4%, the third factor was medical personnel 17.5%, the fourth factor was supporting medical services 15.9%, and the last is inpatient services 11.4%. While the first referral hospital is RSUD Ir. Soekarno with a weight of 31.1%, then Depati Hamzah Hospital with a weight of 27.5%, then Bakti Timah Hospital with 27.3%, and Bakti Wara Hospital with 14.1%.